Interfaces entre redução de danos e educação popular em uma instituição voltada para população em situação de rua em Sorocaba. - Silva, Daniele Cristina da Rocha e (Universidade Federal de São Carlos, 2015)
The main objective of this study was to analyze the conception of education that is implicit in the activities developed by the association "Pode Crer", seeking to understand them from the dialogue between Popular Education and the Health Humanization Policy. The research was conducted by one year of participant observation during which the activities developed by this Association (Drop in, Harm Reduction, Halfway House and some extra activities) were accompanied. The analysis showed several interfaces between the proposal of Harm Reduction and Popular Education on the activities developed by "Pode Crer". It could be also seen how the references used for a better understanding of this Association have a common point: the humanization. Thus, it is an important credibility work of this activity that happens in the invisibility, although with great potential to promote education for the subjects who experience many vulnerabilities from the common management, from shared responsibility, unconditional acceptance, radical listening, horizontal dialogue and aspects that promote meaningful learning at the everyday life of this people
Interfaces between harm reduction and popular education in an institutional focused in the population living on the streets of Sorocaba
Keywords: educação; redução de danos; Política Nacional de Humanização; uso problemático de drogas; população em situação de rua; pessoas desabrigadas; drogas abuso aspectos sociais; humanização dos serviços de saúde; harm reduction; National Humanization Policy; problematic drug use; people living on the streets; CIENCIAS HUMANAS::EDUCACAO